(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
The aim of this paper is to describe a didactic experience developed with a child diagnosed with ASD (Autistic Spectrum Disorder), teaching basic notions of Arithmetic, such as, natural numbers, counting of natural numbers, and order relations between natural numbers: major, minor and equal, and addition, subtraction and multiplication operations. This didactic experience covers a period of approximately two years and, for the teaching of all these notions and procedures, we have used TouchMath method, but with the implementation of other strategies in which multisensory elements were included, in a suitable study environment, according to the needs of the child. The result of this experience was successful, evidencing that the learning of the basic notions of Mathematics, in this case of basic Arithmetic is completely feasible in some children and people with ASD, if appropriated supports are used.